The Influence of Transformational Leadership Style and Work Motivation on Employee Performance at the (BKPSDM) Office of Penajam Paser Utara Regency - Tjatur Ariyanti; Muliyadi Hamid; Habib Muhammad Shahib (Scieclouds Publishing, 2025)
This study aims to analyze and examine the influence of transformational leadership style and work motivation, both partially and simultaneously, on employee performance at the Office of Personnel and Human Resources Development (BKPSDM) of Penajam Paser Utara Regency. The urgency of this research is based on the strategic role of BKPSDM of Penajam Paser Utara as the agency responsible for managing the state apparatus in the buffer zone of the New Capital City of Indonesia (IKN). To address the research objectives, this study adopts a quantitative approach using a survey method. Data were collected through questionnaires distributed to 46 employees as respondents. The data analysis process was conducted using multiple linear regression methods, using SPSS statistical software to process and interpret the findings through validity tests, reliability tests, classical assumption tests, and hypothesis testing (t-test and F-test). The results indicate that, partially, transformational leadership style has a positive and significant effect on employee performance. Similarly, work motivation was found to have a positive and significant effect, emerging as the most dominant variable influencing performance within BKPSDM of Penajam Paser Utara. Simultaneously, both variables were proven to have a significant effect on employee performance with a high F-statistic value. Consequently, enhancing employee performance at BKPSDM of Penajam Paser Utara Regency can be optimized by strengthening inspirational leadership patterns and maintaining sustainable employee work motivation to address the dynamics of future bureaucratic transitions.